Swimming for dementia: an exploratory qualitative study - Hobden, Tanya; Swallow, Mary; Beer, Charlotte; Dening, Tom (SAGE, 2018)
Swimming is a non-weight bearing form of exercise that can be enjoyable and promote physical fitness. This qualitative study investigated a local group established as part of a national dementia swimming initiative. Semi-structured interviews with people with dementia (N=4), carers or companions (N=4) and the organisers and facilitators of the group (N=6) were analysed using thematic analysis. This revealed four main themes: (1) the pleasure of swimming and its benefits as a form of exercise and for building confidence and empowering participants; (2) the importance of insight and empathy in creating a safe and secure experience; (3) the impact of dementia; and (4) how participants valued being part of a group ‘all in the same boat’. ‘Dementia friendly swimming’ appears to be a valuable form of exercise but it requires considerable preparation and support to make it happen.